Hegemony of Involvement of Tafsir in Political Identity - Saifuddin Herlambang; Syamsul Kurniawan (UIN Sunan Kalijaga Yogyakarta, 2018)
Tafsir is a process of text transmission that is inseparable from the ideological and theoretical framework as well as the influence of socio-political conditions and intellectual traditions of interpreters in which the interests will always be present in all the transmission process. This research focuses on the clarity of interpretation in identity politics, which departs from the writer’s anxiety about the phenomena of dragging tafsir in identity politics, as well as the prevalent trends occurring today in Indonesian politics as in the context of the Jakarta Local Election where the QS al-Maidah (5) verse 51 is not only a debatable issue but had also dragged the legitimacy of whether or not to vote for non-Muslim leaders. This research is a qualitative study with descriptive approach, which is hermeneutically analyzed.[Tafsir merupakan proses transmisi teks yang tak terlepas dari kerangka teoretis ideologis dan pengaruh kondisi sosial politik serta tradisi intelektual penafsir di mana kepentingan akan selalu hadir dalam semua proses transmisi tersebut. Fokus kajian ini adalah tentang keterseratan tafsir dalam politik identitas, yang berangkat dari kegelisahan penulis tentang fenomena keterseretan tafsir dalam politik identitas, sebagaimana kecenderungan yang marak terjadi dewasa ini dalam perpolitikan di Indonesia. Seperti, pada konteks Pilkada DKI Jakarta di mana ayat pada QS al-Maidah (5) ayat 51 tidak hanya menjadi modal perdebatan tetapi juga diseret-seret dalam legitimasi tentang boleh atau tidaknya memilih pemimpin yang non muslim. Kajian ini merupakan kajian kualitatif dengan pendekatan deskriptif, yang dianalisis secara hermeneutika.]